Effect of methane co-feeding on product selectivity of catalytic pyrolysis of biomass - Shafaghat, Hoda; Jae, Jungho; Jung, Sang-Chul; Jeon, Jong-Ki; Ko, Chang Hyun; Park, Young-Kwon (ELSEVIER SCIENCE BV, 2018)
Co-feeding a hydrogen-rich material with biomass feedstock is an effective approach to enhance the pyrolysis process efficiency. In this research, the effect of methane (H/C-eff ratio of 4) co-feeding on product selectivity of catalytic pyrolysis of lignin and yellow poplar was studied at 600 degrees C using HY and HZSM-5/metal-modified HZSM-5 as in-situ and ex-situ catalysts, respectively. Fe, Cu, Zn, and Mo with a 3 wt% loading and Ni with 1, 3, and 5 wt% loadings were incorporated into HZSM-5 by incipient wetness impregnation method. Compared to the nitrogen pyrolysis atmosphere, methane enhanced significantly the level of hydrocarbon (BTEX, benzene derivatives and polyaromatics) production from the cellulose and hemicellulose fractions of biomass. Lignin was selectively converted to alkylphenols in catalytic pyrolysis under methane atmosphere. The maximum hydrocarbon yield of 5.86 wt% was obtained from catalytic pyrolysis of yellow poplar using HY (in-situ) and 1 wt% Ni/HZSM-5 (ex-situ) as catalysts, mainly due to the effects of Ni on enhanced methane activation and an increase in the acid site density of HZSM-5. Meanwhile, the coke content of HZSM-5 was increased in both lignin and yellow poplar pyrolysis by replacing the pyrolysis atmosphere of nitrogen with methane.